2011
DOI: 10.1093/ndt/gfr138
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dialysate calcium concentration on the progression of aortic stiffness in patients on haemodialysis

Abstract: In this study, aortic stiffness progressed with DCa 1.37, while it remained stable with DCa 1.12 over a 6-month period. These results suggest that higher DCa concentrations could be a risk factor for the progression of aortic stiffness in HD patients. In the context of limited oral calcium, the long-term safety of DCa 1.12 on bone metabolism remains to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…tic stiffness. Moreover, it should be kept in mind that several factors, other than PTH, are established determinants of arterial stiffening in patients with endstage renal disease 43) and include malnutrition, chronic volume overload, dialysated calcium and others [44][45][46] . Importantly, in the present study, inclusion of patients with a normal glomerular filtration rate allowed us to exclude most of these confounders.…”
Section: Resultsmentioning
confidence: 99%
“…tic stiffness. Moreover, it should be kept in mind that several factors, other than PTH, are established determinants of arterial stiffening in patients with endstage renal disease 43) and include malnutrition, chronic volume overload, dialysated calcium and others [44][45][46] . Importantly, in the present study, inclusion of patients with a normal glomerular filtration rate allowed us to exclude most of these confounders.…”
Section: Resultsmentioning
confidence: 99%
“…They found that higher dialysate calcium concentration was a risk factor for the progression of aortic stiffness in HD patients. 14 Our previous study enrolled 40 PD patients, with dialysate calcium concentration of 1.25 mmol/L in 20 patients and 1.75 mmol/L in another 20 patients. After 12-month follow-up, low calcium dialysate treatment was associated with reduced number of newly occurring cardiovascular events in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Imbalances between factors that promote and factors that inhibit calcification interact with a positive balance or high concentrations of calcium and phosphate to promote vascular calcification [22,23,24]. Dialysis with high dialysate [calcium] has been associated to progression of arterial stiffness [25] while dialysis with 2.5 mEq/l dialysate calcium for 6 months decreased arterial stiffness [26]. Thus, it seems reasonable to avoid a calcium overload from dialysate in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%